Bank Performance in Achieving Islamic Bank Stability Conditions: Evidence From Islamic Banks in Indonesia - Siyamto, Yudi (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to analyze the effect of Islamic bank performance on Islamic bank stability in Indonesia. Methodology using monthly time series data from OJK Islamic Banking Statistics 2015-2022, this study utilizes ECM and ECT tests to examine the long-run impact and short-run response of operational efficiency, liquidity, and bank size on Islamic bank stability. Findings this study found that the performance of Islamic banks in terms of operational efficiency has a negative and significant effect on the stability of Islamic banks both in the short and long term. Furthermore, liquidity has a positive and insignificant effect on the stability of Islamic banks in the long term, but has a positive and significant effect in the short term. Meanwhile, bank size has a positive and significant effect on the stability of Islamic banks in the long term, but for the short term it has a negative and insignificant effect.